Congenıtal cutis laxa - Fuat Gürkan (Dicle Medical Journal, 2003)
A case report is presenting about a rarely appering disease cutis laxa named also as Dermatomegaly and Generalise Elastosis. As it appears congenitally also seems with the accompaniment of infection, inflamation, collagen tissue diseases, hypersensitivity reactions and treatment with D- penicillamine.